P256 Urinary lithogenic profile and gut and urinary microbiota in patients with inflammatory bowel diseases. (30th January 2023) - Mignini, I; Masucci, L; De Maio, F; Laterza, L; Scaldaferri, F; Settanni, C R; Napolitano, D; Baroni, S; Garcovich, M; Riccardi, L; Gasbarrini, A; Ferraro, P M; et al.
Abstract: Background: Nephrolithiasis (NL) is a common extra-intestinal complication of inflammatory bowel disease (IBD) with recognizable morbidity and mortality. However, its pathogenesis and risk factors are not completely elucidated yet. Because of intestinal malabsorption, enteric hyperoxaluria is a crucial pathogenic mechanism responsible for developing urinary stones in IBD patients. In recent decades, growing evidence has highlighted the association between gut microbiota and NL, with a particular emphasis on the role of some oxalate-degrading bacteria, such as Oxalobacter formigenes, representing the mainstay of the so-called "gut-kidney axis." More recent studies also hypothesize the involvement of urinary microbiota, but no data on IBD patients are available. Thus, we conducted a pilot study to analyse the urinary lithogenic profile in IBD patients and its relationship with gut and urinary microbiota. Methods: Consecutive patients with IBD were prospectively enrolled. The presence of ileoanal pouch, ileostomy, colostomy, or short-bowel syndrome were exclusion criteria. Demographic and clinical data, including previous episodes of NL, were collected. Disease activity was evaluated using Harvey-Bradshaw and Mayo scores for Crohn's disease (CD) and ulcerative colitis (UC). All patients underwent abdominal ultrasound for NL detection, and blood tests of kidney function (creatinine, blood urea nitrogen, creatinine clearance, electrolytes) were also measured, together with 24h-urine collection for lithogenic profile analysis, including calcium oxalate relative saturation ratio (RSRCaOx). In a subgroup of patients, urinary and faecal microbiota were also analysed through 16S rRNA sequencing. Results: 36 patients (20 CD and 16 UC) were enrolled. NL was more frequent in CD than in UC (25% vs. 6.25%). 24-h oxaluria was significantly increased in patients with previous or present NL (p=0.02), and RSRCaOx was significantly higher in CD than in UC (p=0.02) (Figure 1). Gut microbiota analysis revealed a higher relative abundance of Bacteroidetes and a lower abundance of Firmicutes in patients with an elevated RSRCaOx, defined for values more than the median (Figure 2). No statistically significant differences were observed in urinary microbiota composition in relation to high or low levels of RSRCaOx. Conclusion: NL is more common in IBD patients with higher oxaluria levels, confirming oxalate excretion's crucial role in NL pathogenesis. Furthermore, our study reports an association between urinary stone development and Firmicutes/Bacteroidetes imbalance in the gut microbiota, suggesting possible further studies to identify patients at higher risk of NL.